Dictionary Representation of Linguocultural Stereotypes: Communicative Behavior of Russians in Thematic Dictionary of Proverbs - T. G. Nikitina; E. I. Rogaleva; Lixiang Piao (Научный диалог)
The article deals with the problem of optimization of the dictionary description of the stereotypes of the Russian linguoculture, reflected by linguistic units, which is relevant for Russian cultural linguistics and lexicography. The possibilities of solving this problem are shown with a thematic vocabulary systematization of proverbs regulating the communicative behavior of Russians. A review of modern linguoculturological and linguoaxiological studies of paremias reflecting communicative behavior in their projection onto lexicographic practice is carried out. The development of the ideas of paremiographers of the 19th century in modern concepts of thematic dictionaries is shown, special attention is paid to the rubrication of sections and methods of commenting on proverbs of speech-behavioral topics. The author’s version of the classification of proverbial material reflecting the communicative behavior of Russians is given, the expediency of the dispersed arrangement of paremias in the headings representing speech genres and features of communication in certain socio-cultural spheres is substantiated. In accordance with this concept, the system of linguoaxiological parameterization of proverbs, developed by the authors earlier, has been modified. Samples of dictionary macrostates representing the axiologems of the speech-behavioral sphere are given; proverbial material of Internet communication that has not been reflected in dictionaries at the moment is used. The possibilities of using the proposed linguoaxiological parameterization of the material in the bilingual thematic dictionary of proverbs are shown.